Editorial - Aguirre Chávez, Felipe (2024)
When presenting issue 24 of the EDUCA UMCH Magazine, I wish to express that this achievement would not have been possible without the unconditional support of the editorial team and the preference of academics from various parts of the world. Through collaborative and persistent work, we have demonstrated that, as the Spanish philosopher Miguel de Unamuno said, "The way to hit the nail once is to hit the horseshoe a hundred times."